Implementación de un sistema web de información academico para el Colegio Técnico Intercultural Bilingüe Fiscomicional Abya-Yala - Lopez Tapia, Edison Javier (2008)
World Wide Web (or the “Web”) is a hypertext and / or document system hypermedia linked and accessible through the Internet. With a browser Web, a user views Web pages that may contain text, images, videos and other multimedia content and navigate through them using hyperlinks. This medium proposed since the 1940s and used until 1980 As a technological operational support for the distribution of information, it has had exorbitant growth in recent years, being one of the means for communication at a lower cost and faster.